Gradient-independent Wnt signaling instructs asymmetric neurite pruning in C. elegans - Menghao Lu; Kota Mizumoto (eLife, 2019)
During development, the nervous system undergoes a refinement process by which neurons initially extend an excess number of neurites, the majority of which will be eliminated by the mechanism called neurite pruning. Some neurites undergo stereotyped and developmentally regulated pruning. However, the signaling cues that instruct stereotyped neurite pruning are yet to be fully elucidated. Here we show that Wnt morphogen instructs stereotyped neurite pruning for proper neurite projection patterning of the cholinergic motor neuron called PDB in C. elegans. In lin-44/wnt and lin-17/frizzled mutant animals, the PDB neurites often failed to prune and grew towards the lin-44-expressing cells. Surprisingly, membrane-tethered lin-44 is sufficient to induce proper neurite pruning in PDB, suggesting that neurite pruning does not require a Wnt gradient. LIN-17 and DSH-1/Dishevelled proteins were recruited to the pruning neurites in lin-44-dependent manners. Our results revealed the novel gradient-independent role of Wnt signaling in instructing neurite pruning.